Efficiency and productivity in the takaful and insurance industries in Pakistan: a comparitive analysis - Ashraf, Mohammad Saleem (2019)
The comparisons of the efficiency insurance and takaful films which are operating simultaneously in the financial system need further investigation. The takaful industry is new player in the market which is struggling on its profitability specifically for developing country like Pakistan. This study investigates the existence of technical efficiency (TE), pure technical efficiency (PTE) and scale efficiency (SE) by applying Data Envelopment analysis (DEA) for the insurance and takaful sector from 2008 to 2016. This study measures the productivity change with Malmquist productivity index (MPI) for both insurance and takaful sector. In addition, this study also aims to identify the firm level attributes (asset size (SIZE), market share (MS), profitability (ROE) and leverage (LEV)) by Tobit Regression which determine the efficiency of insurance and takaful industry for Pakistan. The data for the fourteen insurance and four takaful firms is collected from the annual reports of the firms, State Bank of Pakistan reports and Insurance Association of Pakistan reports. The results highlight that takaful firms have more technical and pure technical efficiency as compared to the insurance firms whereas insurance firms attain more scale efficiency score for the study period. The takaful industry records the higher productivity than insurance firms measured by MPI. The results show the negative significant relation between SIZE and TE, SE of insurance and PTE of takaful and positive with TE and SE of takaful. MS is positive and significant with TE, PTE and SE of insurance and PTE of takaful. ROE is negative and significant with PTE of insurance and TE and SE of takaful. LEV is significant except to SE of insurance. The mixed results imply that policy makers and practitioners should develop different prudential regulations to improve scale efficiency especially for takaful industry by enhancing their branch network, new products development for adaptation of latest techniques and technology.